Big Data Computing and Communications First International Conference, BigCom 2015, Taiyuan, China, August 1-3, 2015, Proceedings - Wang, Yu; Xiong, Hui; Argamon, Shlomo; Li, XiangYang; Li, JianZhong (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the proceedings of the First International Conference on Big Data Computing and Communications, BigCom 2015, held in Taiyuan, China, in August 2015. The 41 papers presented in this volume were carefully reviewed and selected from 74 submissions. They were organized in topical sections named: wireless communication and networks; database and big data; smart phone and sensing application; security and privacy; architecture and applications; sensor networks and RFID; social networks and recommendation; signal processing and pattern recognition; and routing and resource management.